The Implementations of Suitable Cutting Parameters by Grinding of Titanium VT9 with Impact on Surface Integrity - Stancekova, Dana; Rudawska, Anna; Neslušan, Miroslav; Mrázik, Jozef; Janota, Miroslav (Manufacturing Technology Journal, 2019)
Despite the fact that Titanium alloys are frequently used in medicine, aviation industry and also in machine manufacture due to their strength and resistance against external influences. Moreover, their innovation to obtain better and more suitable parameters still proceeds. Regarding their mechanical properties, they are considerably less machinable which affects surface integrity of a machined area. That is why a proper selection of a machine tool and cutting conditions are extremely important. This paper deals with a finishing grinding process of the material VT9 by means of specific grinding wheels 5TG and DIA under specified cutting conditions. Based on experimental verifications it can be defined which grinding Wheel is more suitable in specific conditions with an impact on integrity of the ground surface. From the standpoint of grinding parameters such as surface roughness, thermal impact and acting of cutting forces as well as arising residual stress in the surface layer are key for surface integrity.
Keywords: Grinding; Cutting forces; surface roughness; residual stress